2013
DOI: 10.1080/10942912.2011.631254
|View full text |Cite
|
Sign up to set email alerts
|

A Fourier Transform Infrared Spectroscopy Method for Analysis of Palm Oil Adulterated with Lard in Pre-Fried French fries

Abstract: Fourier transform infrared spectroscopy with attenuated total reflectance accessory was used to detect the presence of lard in French fries pre-fried in palm oil adulterated with lard. A Fourier transform infrared calibration model was obtained using partial least squares for prediction of lard in a blend mixture of lard and palm oil. The coefficient of determination (R 2 ) of 0.9791 was obtained with 0.5% of detection limit. The error in calibration expressed with root mean square error of calibration was 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 17 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…e peak at 1117 cm −1 on the contrary is attributed to the out-of-plane CH bending; according to [13], a higher abundance of oleic acyl groups in oil (18 : 1) would evidence a reduction in the peak intensity. Lard typically contains 42% of oleic acid whilst palm olein oil comprises of 38% [25]; this suggests the inverse relationship between the peak intensity and lard concentrations. Other peaks at 1236 cm −1 and 1159 cm −1 are linked to the stretching of C-O group in esters.…”
Section: Resultsmentioning
confidence: 99%
“…e peak at 1117 cm −1 on the contrary is attributed to the out-of-plane CH bending; according to [13], a higher abundance of oleic acyl groups in oil (18 : 1) would evidence a reduction in the peak intensity. Lard typically contains 42% of oleic acid whilst palm olein oil comprises of 38% [25]; this suggests the inverse relationship between the peak intensity and lard concentrations. Other peaks at 1236 cm −1 and 1159 cm −1 are linked to the stretching of C-O group in esters.…”
Section: Resultsmentioning
confidence: 99%
“…Palm oil of FTIR spectrum had aliphatic hydrocarbon bonds such as -CH 3 at the area of 2951 cm -1 and 1376 cm -1 then -CH 2 at the area of 2852 cm -1 and 1476 cm -1 . There also were occurred aliphatic ester bonds such as -C=O in the area of 1743 cm -1 and -C-O in the area of 1150 cm -1 that corresponded as the literature [24,25].…”
Section: Resultsmentioning
confidence: 53%
“…The chemical reaction between palm oil and bioplastics starch shows an intensity of -C=O bond of aliphatic ester developed from palm oil in the area of 1747 cm -1 . Palm oil has carbonyl stretching of the triacylglycerol ester linkage that could attach into starch based bioplastics because of gelatinization process [25]. However, there was no significant difference from the FTIR spectra of each bioplastic with increasing palm oil percentage.…”
Section: Resultsmentioning
confidence: 90%
“…Finger printing regions indicate that no two oils have the same FTIR spectra, in terms of either number of peaks or maximum peak intensity. The finger printing region of various edible oils and fat including palm oil (Che Man et al , 2014), palm kernel olein (Manaf et al , 2007), coconut oil (Manaf et al , 2007), olive oil (Maggio et al , 2010), sunflower oil (Che Man et al , 2011), sesame oil, rice bran oil (Che Man et al , 2011), peanut oil, soyabean oil, corn oil (Vasconcelos et al , 2015), trans fat (Pandey and Jariwala, 2015), beef fat and lard (Che Man et al , 2011) were reported in the literatures. On comparing the spectra of ghee with those of the oils and fats reported in the literatures, substantial differences were noticed in number of peaks and/or their position.…”
Section: Resultsmentioning
confidence: 99%